The Influence Of Promotion Strategies And Service Quality On Consumer Purchase Decisions At Bintang Mulia Jaya Dealer Lubuk Beringin Manggul - M. Agel Al Haffizh Ramadhan; Hayani Hayani; Iskandar Iskandar (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the influence of promotion strategy and service quality on consumer purchase decisions at Honda Dealer Bintang Mulia Jaya Lubuk Beringin Manggul, Lahat. The type of research is associative quantitative with a population of 157 consumers and a sample of 61 respondents determined using Slovin's formula with a 10% margin of error. Promotion strategy indicators include advertising, personal selling, sales promotion, and public relations. Service quality indicators include reliability, responsiveness, empathy, tangibles, and assurance. Purchase decision indicators include product stability, buying habits, recommendations, and repeat purchases. Data analysis methods used multiple linear regression, t-test, f-test, and coefficient of determination. The results showed that both promotion strategy and service quality have a significant positive influence, partially and simultaneously, on consumer purchase decisions.